Exploring the Utilization and Acceptance of Learning Management System for In-Service Training of Primary School Teachers - Muhammad Aslam, (JCTE, 2025)
Learning Management Systems (LMS) is emerging internet technology that facilitating the instructions in blended, distance and face to face learning. The primary purpose of this study was to investigate the utilization and acceptance of LMS for in-service training of Primary School Teachers (PSTs) and contribution of ease to use and usefulness of LMS in enhancing attitude towards use of LMS at Quaid-e-Azam Academy for Educational Development (QAED) Punjab. The present study was a quantitative research and cross sectional survey design was used. The data were collected using adapted questionnaire of Trayek and Hassan (2013), which covered three variables ease of use, usefulness and attitude toward use of LMS. The respondents of this study were 417 Primary School Teachers (PSTs) of district Okara and stratified random sampling technique was used for sampling. The data were collected through online Google survey form. After that, the data were analyzed using SPSS and different statistics techniques to meet the study objectives. The results indicated that teachers were somewhat agree and slightly satisfied with the usefulness and ease to use of LMS in their training. Further, it was investigated that usefulness and ease to use of LMS had significant and positive contribution in developing and enhancing attitude toward use of LMS in training. It was recommended that the management of QAED Punjab increase the purposefulness, usefulness, easy use and access of LMS among teachers in training.